Intrinsic and extrinsic aspects of the abnormal tissue healing process (Journal of Face Aesthetics, 2025)
Introduction. Hypertrophic scars and keloids are consequences of abnormalities in the healing process and tissue repair, characterized by excessive fibrosis present throughout the wound distribution. In this sense, there are several extrinsic and intrinsic factors that corroborate the hypertrophic healing process.Aim. To analyze which morphological and metabolic factors accentuate the incidence of hypertrophic scars and keloids in healing processes in the last five years.Material and methods. Systematic review study without meta-analysis outlined by the PRISMA protocol and registered in PROSPERO from the literature bases in the broad area of ​​knowledge of Health Science: PubMed, Virtual Health Library (BVS), Periódico Capes and LILACS. The research was carried out by crossing the following descriptors: “plastic surgery”, “hypertrophic scar” and “healing”, in which articles written and published from 2020 to 2023 were used.Results. Molecular aspects of tissue modulation, hypertension, genetic factors of single nucleotide polymorphisms and factors related to lifestyle can influence the occurrence of abnormal scars.Conclusions. Hypertrophic scars and keloids are related to extrinsic and intrinsic factors, such as metabolic causes and the patient's postoperative course.
Keywords: plastic surgery; hypertrophic scar; healing